(untitled) (GEON Journal (Management, Organizations and Business), 2015)
This paper presents the results found in the development of the research made to “Comercializadora 4x4”, microenterprise from Villavicencio Meta. Its objective was redesign the administrative and organizational structure of the enterprise such that the processes be strengthened and the company be routed to the broadening of its market. As well proposal as development of the research were performed within administrative theories wich routed the elaboration of a complete diagnostic from the company, the formulation strategic platform and the proposal of a organizational redesign directed to the processes. Investigation involved the participation from enterprise staff and consulting from specialist of the Llanos University.